Donor killer immunoglobulin-like receptor genes and reactivation of cytomegalovirus after HLA-matched hematopoietic stem-cell transplantation: HLA-C allotype is an essential cofactor - Behrendt, Carolyn E.; Nakamura, Ryotaro; Forman, Stephen J.; Zaia, John A. (Frontiers in Immunology, 2013)
Natural Killer (NK) cells whose killer immunoglobulin-like receptors (KIR) recognize human leukocyte antigen (HLA) ligand are “licensed” for activity. In contrast, non-licensed NK cells display KIRs for which ligand is absent from the self genotype and are usually hyporesponsive. Surprisingly, non-licensed cells are active in tumor control after hematopoietic stem-cell transplantation (HSCT) and dominate NK response to murine cytomegalovirus (CMV) infection. From those reports, we hypothesized that control of human CMV early after HSCT is influenced by donor KIR genes whose HLA ligand is absent-from-genotype of HLA-matched donor and recipient. To investigate, we studied CMV reactivation through Day 100 after grafts involving CMV-seropositive donor and/or recipient. A multivariate proportional rates model controlled for variability in surveillance and established covariates including acute graft-versus-host disease; statistical significance was adjusted for testing of multiple KIRs with identified HLA class I ligand (2DL1, 2DL2/3, 2DS1, 2DS2, full-length 2DS4, 3DL1/3DS1, 3DL2). Among HSCT recipients (n=286), CMV reactivation-free survival time varied with individual donor KIR genes evolutionarily-specific for HLA-C: when ligand was absent from the donor/recipient genotype, inhibitory KIRs 2DL2 (P<0.0001) and 2DL1 (P=0.015) each predicted inferior outcome, and activating KIRs 2DS2 (P<0.0001), 2DS1 (P=0.016), and 2DS4 (P=0.016) each predicted superior outcome. Otherwise, with ligand present-in-genotype, donor KIR genes had no effect. In conclusion, early after HLA-matched HSCT, individual inhibitory and activating KIR genes have qualitatively different effects on risk of CMV reactivation; unexpectedly, absence of HLA-C ligand from the donor/recipient genotype constitutes an essential cofactor in these associations. Being KIR and HLA-C specific, these findings are independent of licensing via alternate NK cell receptors (NKG2A, NKG2C) that recognize HLA-E.